2019
DOI: 10.1096/fj.201802619rr
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib kills liver cancer cells by disrupting SCD1‐mediated synthesis of monounsaturated fatty acidsviathe ATP‐AMPK‐mTOR‐SREBP1 signaling pathway

Abstract: Sorafenib is a multikinase inhibitor that is effective in treating advanced liver cancer. Although its mechanism of action through several established cancer‐related protein kinase targets is well‐characterized, sorafenib induces variable responses among human tumors, and the cause for this variation is yet unknown. To investigate the underlying mechanisms, we applied mass spectrometry‐based proteomic analysis to Huh7.5 human liver cancer cells and found that sorafenib significantly affected the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 46 publications
3
67
0
Order By: Relevance
“…Inhibition of these targets, such as VEGFR and PDGFR, largely contributes to its clinical efficacy [65]. In recent years, other novel molecular targets of sorafenib have been discovered [16][17][18][19]. We previously mined the Connectivity Map (CMap) database to explore the potential molecular target(s) of sorafenib and found that sorafenib indirectly inhibited HDAC activity in HCC cells [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of these targets, such as VEGFR and PDGFR, largely contributes to its clinical efficacy [65]. In recent years, other novel molecular targets of sorafenib have been discovered [16][17][18][19]. We previously mined the Connectivity Map (CMap) database to explore the potential molecular target(s) of sorafenib and found that sorafenib indirectly inhibited HDAC activity in HCC cells [66].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of the components of cell survival pathways, such as myeloid cell leukemia-1 (MCL-1), and upregulation of pro-apoptotic Bcl-2 family proteins, such as p53 upregulated modulator of apoptosis (PUMA) and Bcl-2-interacting mediator of cell death (BIM), are associated with the apoptosis-inducing effects of sorafenib in HCC [14,15]. Recently, several novel anticancer targets of sorafenib have been identified, such as 5-hydroxytryptamine (5-HT) receptor [16], stearoyl coenzyme A desaturase 1 (SCD1) [17], and protein biosynthesis [18]. Especially, sorafenib is identified as a system x c − (a cell-surface Na + -independent cystine-glutamate antiporter) inhibitor that leads to endoplasmic reticulum (ER) stress and ferroptosis (an iron-dependent form of non-apoptotic programmed cell death) [19].…”
Section: Introductionmentioning
confidence: 99%
“…The expressions of SREBP-1 and FAS were enhanced in the palmitate treatment than the control, but those were significantly decreased under the CPEW, CPEF or hesperidin. The CPEW, CPEF and hesperidin treatment also increased p-AMPK/AMPK ( Figure 9E), a main controlling upstream signaling on mTORC1 and ER stress and its associated hepatic lipogenesis genes [17]. Supplementation with CPEW, CPEF, and hesperidin reversed the elevations of mRNA factors involved in fatty acid synthesis.…”
Section: The Major Components Of Cpe and Hesperdin Regulate Ampk Actimentioning
confidence: 82%
“…Consistent with previous findings that the knockout of TSC1 or TSC2 induces UPR, resulting in mTOR-associated feedback inhibition of insulin action [22], it is noted that nutrient overload induces ER stress response in an mTORC1-dependent manner. In addition, chronic liver ER stress was observed in the steatosis of mice strains with genetically deficient in leptin as well as genetically modified IRE1/XBP1, PERK/eIF2α and ATF6 signaling pathways [17,20]. The ER stress response is one of the main features of pathological conditions associated with obesity and NAFLD [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…All tests were performed in triplicate. The values of relative cell viability were calculated as percentages of absorbance from the treated samples to absorbance from the vehicle control [21].…”
Section: X-ray Crystallographic Analysismentioning
confidence: 99%